تطوير العلاقة بزبائن المؤسسة الرياضية على ضوء معايير إدارة الجودة الشاملة - عزوز، محمد (جامعة زيان عاشور الجلفة - معهد علوم وتقنيات النشاطات البدنية والرياضية, 2015)
تلعب الجودة عاملا أساسيا في خلق الميزة التنافسية، كما تركز إدارة الجودة الشاملة على التحسين المستمر وهو مفهوم يحتم على الإدارة أن تطور وتعزز العمليات التي سوف تؤدي إلى التحسين المستمر لجودة الخدمات المقدمة، ويعد التحسين للجودة من أهم أهداف الإدارة الرياضية لبلوغ الجودة المطلوبة حيث أن إدارة الجودة الشاملة تقضي بأن يكون كل عنصر في المؤسسة الرياضية وكل فعالية وقسم والذي هو جزء من الخدمة خاضعا لتطبيقات مبادئ إدارة الجودة. ولقد اخترنا ميدان الدراسة المسبح الأولمبي بولاية الجلفة وبلغت عينة الدراسة (60) زبونا.
Quality is a key factor for any competitive advantage, Total quality management (TQM), also focuses on continuous improvement, a concept that means management must develop and enhance the processes that will lead to constant improvement in the quality of the provided services. Moreover, quality improvement is one of the main targets for achieving the required quality. Total quality management decrees that every element in the Organization, activity and component which is part of the service or product should be subject to application of quality management principles. The study has sought to recognize the extent of (TQM) effect on the customer capital. Piscine Olympique in Wilaya Djelfa has been chosen to the study sample. It is consisted of (60) people.
Keywords: إدارة الجودة الشاملة -- التنظيم الإداري -- المؤسسة الرياضية